A process evaluation of a vitality intervention among older hospital workers. (19th October 2011) - Strijk, Jorien; Proper, Karin; van Mechelen, Willem; van der Beek, Allard
Abstract : Objectives: Evaluating the process of a vitality intervention, consisting of a vigorous physical activity component and a yoga programme, among older workers. Methods: This process evaluation was part of a RCT among 730 workers aged ≥45 years from two academic hospitals. 367 workers were randomised into the intervention group and received a 6-months intervention consisting of a Vitality Exercise Programme (VEP) combined with three visits to a Personal Vitality Coach (PVC), aimed at goal setting, feedback, and problem solving. The VEP consisted of a guided yoga and workout session, and aerobic exercising without direct face-to-face instruction, all once a week. To gain insight into the context, dose delivered, fidelity, reach, dose received, and participants' attitude, data was collected by means of questionnaire, VEP attendance registration forms, and coaching registration forms. Results: The reach of the yoga sessions, workout sessions and PVC visits was 70.6%, 63.8%, and 89.6%, respectively. There were substantial differences between the two locations. The dose received for yoga was 10.4 and for the workout 11.1 sessions. Attendance rates for yoga and workout sessions were 51.7% and 44.8%. This rate differed between the locations for yoga (63.2% vs 46.5%). Workers attended on average 2.7 PVC visits. Overall, workers were satisfied with the intervention components and rated the sessions as following: 7.5 for yoga, 7.8 for workout sessions, and 6.9 for PVC visits. Conclusions: Workers were willing to attend the guided group sessions and the PVC visits, although there were differences between the locations. Overall, workers were positive about the intervention.